Education of preschool and elementary teachers on the use of adaptive gamification in science education. (22nd January 2022) - Zourmpakis, Alkinoos-Ioannis; Papadakis, Stamatios; Kalogiannakis, Michail
The use of games regarding education is not something new. Their use, especially in the early stages of the education system, is notably widespread in helping students learn and develop various skills. Although students are considered the centre of teaching, the teacher plays a central key role. He/she is called upon to care and understand the needs of each individual student, provide the proper learning material and evaluate the whole learning process. We propose exploring how active and pre-service teachers design and integrate adaptive gamified environments into teaching science education.